Time evolution of cytokine profiles associated with mortality in COVID-19 hospitalized patients - Sánchez-de Prada, Laura; Gorgojo-Galindo, Óscar; Fierro, Inmaculada; Martínez-García, Ana María; de Quintana, Guillermo Sarmentero-López; Gutiérrez-Bustillo, Rocío; Pelaez-Jareño, María Teresa; Álvarez-Fuente, Elisa; Gómez-Sánchez, Esther; Tamayo, Eduardo; Tamayo-Velasco, Álvaro; Martín-Fernández, Marta (Frontiers in Immunology, 2022)
Background: High cytokine levels have been associated with severe COVID-19 disease. Although many cytokine studies have been performed, not many of them include combinatorial analysis of cytokine profiles through time . In this study we investigate the association of certain cytokine profiles and its evolution, and mortality in SARS-CoV2 infection in hospitalized patients. Methods: Serum concentration of 45 cytokines was determined in 28 controls at day of admission and in 108 patients with COVID-19 disease at first, third and sixth day of admission. A Principal Component Analysis (PCA) was performed to characterize cytokine profiles through time associated with mortality and survival in hospitalized patients. Results: At day of admission non-survivors present significantly higher levels of IL-1α and VEGFA (PC3) but not through follow up. However, the combination of HGF, MCP-1, IL-18, eotaxine, and SCF (PC2) are significantly higher in non-survivors at all three time-points presenting an increased trend in this group through time. On the other hand, BDNF, IL-12 and IL-15 (PC1) are significantly reduced in non-survivors at all time points with a decreasing trend through time, though a protective factor. The combined mortality prediction accuracy of PC3 at day 1 and PC1 and PC2 at day 6 is 89.00% (p<0.001). Conclusions: Hypercytokinemia is a hallmark of COVID-19 but relevant differences between survivors and non-survivors can be early observed. Combinatorial analysis of serum cytokines and chemokines can contribute to mortality risk assessment and optimize therapeutic strategies. Three clusters of cytokines have been identified as independent markers or risk factors of COVID mortality.